Pengaruh proporsi sari kulit manggis (Garcinia mangostana L.) dan gula terhadap sifat kimia dan organoleptik minuman isotonik air kelapa - Titus Tirtawan; Kejora Handarini; Bambang Sigit Sucahyo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Isotonic drinks made from coconut water are products that are widely liked, but there are not many flavor variants, so it is necessary to look for alternative ingredients to add flavor variations, so we need mangosteen rind juice as one of the ingredients that can be used as a flavor enhancer. This research aims to determine the effect and best proportion of mangosteen peel juice on the chemical and organoleptic properties of coconut water. This research method is laboratory experimental which uses an experimental design: Completely Randomized Design (CRD) 1 Factor which consists of 4 levels, namely Sugar concentration: Mangosteen Peel P1 = 20% : 15%, P2 = 15% : 20%. P3 = 10%:25%, P4: = 5% : 30%, and this research was carried out in 3 repetitions. The parameters tested are chemical properties: pH test, Total Sugar test, Sodium test, and Potassium test as well as organoleptic properties consisting of: taste, aroma, color. The research results show that the use of 30% mangosteen peel extract has chemicalÂ characteristics. Meanwhile, the best in terms of physical characteristics and organoleptics is the use of 20% mangosteen peel juice. The use of mangosteen peel juice increases potassium and sodium levels and also increases the chemical properties. This shows that mangosteen peel juice has great potential as an additional ingredient in isotonic drinks.